Discovery of novel zeolites for natural gas purification through combined material screening and process optimization. Issue 5 (24th March 2014) - First, Eric L.; Hasan, M. M. Faruque; Floudas, Christodoulos A.
<x xml:space="preserve">Abstract</x> An efficient computational screening approach is proposed to select the most cost‐effective materials and adsorption process conditions for CH4/CO2 separation. The method identifies eight novel zeolites for removing CO2 from natural gas, coalbed methane, shale gas, enhanced oil recovery gas, biogas, and landfill gas sources. The separation cost is minimized through hierarchical material screening combined with rigorous process modeling and optimization. Minimum purity and recovery constraints of 97 and 95%, respectively, are introduced to meet natural gas pipeline specifications and minimize losses. The top zeolite, WEI, can recover methane as economically as $0.15/MMBTU from natural gas with 5% CO2 to $1.44/MMBTU from natural gas with 50% CO2, showing the potential for developing natural gas reservoirs with higher CO2 content. The necessity of a combined material selection and process optimization approach is demonstrated by the lack of clear correlation between cost and material‐centric metrics such as adsorption selectivity. © 2014 American Institute of Chemical Engineers AIChE J, 60: 1767–1785, 2014